Early-onset pneumonia after out-of-hospital cardiac arrest. Issue 6 (June 2015) - Kakavas, S.; Mongardon, N.; Cariou, A.; Gulati, A.; Xanthos, T.
Summary: Early-onset pneumonia (EOP) is a common complication after successful cardiopulmonary resuscitation. Currently, EOP diagnosis is difficult because usual diagnostic tools are blunted by the features of post-cardiac arrest syndrome and therapeutic hypothermia itself. When the diagnosis of EOP is suspected, empiric antimicrobial therapy should be considered following bronchopulmonary sampling. The onset of EOP increases the length of mechanical ventilation duration and intensive care unit stay, but its influence on survival and neurological outcome seems marginal. Therapeutic hypothermia has been recognized as an independent risk factor for this infectious complication. All together, these observations underline the need for future prospective clinical trials to better delineate pathogens and risk factors associated with EOP. In addition, there is a need for diagnostic approaches serving the accurate diagnosis of EOP. Highlights: EOP after cardiac arrest possesses distinct epidemiological characteristics. Therapeutic hypothermia is highly suspected as an independent risk factor for EOP. The diagnosis relies on respiratory sampling, clinical and radiological examination. Positive direct microscopy or a high clinical suspicion justifies empirical antibiotics. Empirical treatment depends on local epidemiology and the patient's medical history.